"Better to kill them off at once": race, violence, and human rights in antebellum western state constitutional conventions. Issue 1 (2nd January 2019) - Siddali, Silvana R.
ABSTRACT: My paper argues that delegates to antebellum western state constitutional conventions, in both slave and free states, expressed violent, even homicidal ideas about free black people. They predicted and described mass exterminations, lynching, and even a race war. These delegates sought to enshrine coercive measures in their state constitutions, including re-enslavement and forcible removals, and they employed ferocious language to support their arguments. My paper explores the delegates' efforts to mount legal and constitutional justifications for violence toward free black people. I compare the language in antebellum western conventions to coeval debates in other regions. Although no state legitimized lynching, let alone genocide, these debates provide a useful window into the delegates' efforts to find constitutional justifications for the removal – or even extermination – of free black people from the new western states.